2021
DOI: 10.1039/d1sc03851f
|View full text |Cite
|
Sign up to set email alerts
|

Cross-dehydrogenative N–N couplings

Abstract: For more than a century, the dehydrogenative formation of N–N bonds has remained mostly confidential. Several cross-dehydrogenative N–N coupling methods have appeared recently, promising a soon to come broad applicability of the concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…has been developed. 4 However, this method has limitations on the substrate scope due to harsh reaction conditions and potential side reactions such as the formation of C−N bonds. To expand the reaction scope, the aerobic Cu/Fe-catalytic systems were developed using oxygen instead of strong oxidants (Scheme 1A).…”
Section: ■ Introductionmentioning
confidence: 99%
“…has been developed. 4 However, this method has limitations on the substrate scope due to harsh reaction conditions and potential side reactions such as the formation of C−N bonds. To expand the reaction scope, the aerobic Cu/Fe-catalytic systems were developed using oxygen instead of strong oxidants (Scheme 1A).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Assessment of different ligands showed that the best result could be obtained with 4,7-Diphenyl-1,10-phenanthroline (BPhen) as the ligand. Deep optimization of the light source led to 91% yield of the NÀ N coupling product when the reaction mixture was irradiated at 390-395 nm in the presence of Co(OAc) 2 • H 2 O with BPhen in MeCN (entries [9][10][11][12][13][14][15][16][17][18]. Controlling experiments showed that the NÀ N coupling reaction could not occur in the absence of either the irradiation or cobalt catalyst, indicating that both of which are necessary for the transformation (entries 19-20).…”
Section: Resultsmentioning
confidence: 99%
“…[10] Recently, electrolysis method [11] has also been reported to realize the direct NÀ N coupling reaction. [12] On the other hand, the aerobic oxidation has been regarded as one of the most straightforward and environmental friendly strategies to build up chemical bonds as that the utility of molecular oxygen (O 2 ) as the terminal oxidant is a green and sustainable reagent in organic transformations. [13] Stahl group developed an elegant aerobic NÀ N coupling of carbazoles and diarylamines in the combination use of CuBr • Me 2 S and ligand [14] (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous N–X (O, C, N, H) bond cleavage reactions used for establishing inter- and intra-molecular N–N bonds have been summarized by the Lu group 27 and various cross dehydrogenative N–N coupling reactions have been reviewed by Patureau and co-workers. 28 Of late, Zhao 29 and Ryan 30 and coworkers reported a greener biosynthetic route for N–N formation.…”
Section: Introductionmentioning
confidence: 99%